2013
DOI: 10.1186/1476-4598-12-128
|View full text |Cite
|
Sign up to set email alerts
|

A novel Hsp90 inhibitor AT13387 induces senescence in EBV-positive nasopharyngeal carcinoma cells and suppresses tumor formation

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is an epithelial malignancy strongly associated with Epstein-Barr virus (EBV). AT13387 is a novel heat shock protein 90 (Hsp90) inhibitor, which inhibits the chaperone function of Hsp90 and reduces expression of Hsp90-dependent client oncoproteins. This study aimed to evaluate both the in vitro and in vivo antitumor effects of AT13387 in the EBV-positive NPC cell line C666-1.ResultsOur results showed that AT13387 inhibited C666-1 cell growth and induced cellular senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…Likewise, LBH589 activates ERK to disrupt a phosphatase PP1a-HDAC6 complex, and accelerates the turnover of HDAC6 in prostate cancer cells [61]. In addition, HDAC6 is lost upon inhibition of HSP90 in EpsteinBarr virus-positive nasopharyngeal carcinoma cells [62].…”
Section: Reviewmentioning
confidence: 99%
“…Likewise, LBH589 activates ERK to disrupt a phosphatase PP1a-HDAC6 complex, and accelerates the turnover of HDAC6 in prostate cancer cells [61]. In addition, HDAC6 is lost upon inhibition of HSP90 in EpsteinBarr virus-positive nasopharyngeal carcinoma cells [62].…”
Section: Reviewmentioning
confidence: 99%
“…AT13387, a nonansamycin HSP90 inhibitor provided by Astex Pharmaceuticals, was reported to suppress cell growth of various cancer types (non-small-cell lung carcinoma, and nasopharyngeal carcinoma) by previous reports (28,29). No previous study reported, the effectiveness of AT13387 for cholangiocarcinoma cell lines; however, Shapiro and colleagues reported a phase I study of AT13387 for solid tumors, including one cholangiocarcinoma patient.…”
Section: Discussionmentioning
confidence: 87%
“…Log P values of the two synthesized complexes were calculated using the ChemDraw Ultra 8.0 (CambridgeSoft Coporation, MA, USA). tivated in M199 medium supplemented with 20 g/ml ECGS, 90 g/ml heparin, 20% heat-inactivated fetal bovine serum and 1% P/S [26][27][28]. Cell viability was measured by MTT assay to evaluate the cytotoxicity of the complexes.…”
Section: Metal Complexesmentioning
confidence: 99%